PTEN inactivation by germline/somatic c.950_953delTACT mutation in patients with Lhermitte–Duclos disease manifesting progressive phenotypes. (25th October 2013) - Chen, X.‐Y.; Lu, F.; Wang, Y.‐M.; Yang, Y.; Wei, G.‐Q.; Wu, D.; Wang, L.‐F.; Wu, Y.‐M.
<x xml:space="preserve">Abstract</x> Lhermitte–Duclos disease (LDD), a neurological manifestation of Cowden syndrome (CS), is a rare and benign cerebellar disorder, featured by dysplastic cerebellar ganglion cells which replace granular and Purkinje cells. Phosphatase and Tensin Homolog (PTEN) is confirmed as the susceptibility gene for CS which represents the most complex features and is not easily recognizable. We reported two index patients with LDD diagnosed either in an isolated form or coexist with CS. These two patients displayed progressive though comparable phenotypes and were found to carry an identical PTEN c.950_953delTACT mutation in either germline or somatic sources of DNA, respectively. Negative or moderate expression levels of PTEN were validated by immunohistochemistry in the corresponding patients' affected tissues. This study has revealed a novel pathogenicity locus to LDD/CS as a candidate for early molecular diagnosis. In addition, the differential PTEN mutation status with corresponding LDD phenotypes suggests a potential correlation between germline or somatic mutation and coexisting LDD/CS or isolated LDD, respectively. Furthermore, our data could lend some reference to the underlying molecular mechanism of LDD pathogenesis in the future.